Efforts to Increase Public Awareness in All Fields Using the SWOT Analysis Method in Cibatu Cikembar Village - Yepi Sopian; Ichsan, Moch; Waldah, Siti Hani; Hasanah, Uus Uswatun; Maskupah; Laelasari, Ely; Harisman, Haris (Indonesian Journal of Society Development, 2024)
Student Work Lectures (KKM) are a form of cross-disciplinary and sectoral community service carried out by students at certain times and places. Implementation of KKM training generally lasts between one and two months and occurs in city-level areas. The Directorate General of Further Education throughout Indonesia hopes that every university can implement KKM as an extracurricular activity that strengthens the tri dharma of further education, in particular: training, exploration and local regional administration. Social intervention is an approach used in community service. Social intervention is a planned change effort towards individuals, groups and society based on kinship and independence. The essence of social mediation is to work on the ability of friendship (humans, groups, society) which is the goal of progress. It is generally accepted that achieving a state of well-being will be easier for someone whose social functioning is good. Data collection is the most important stage of intervention because this is where social workers gather the information needed to solve the problem. This can help regions make progress in various fields, especially education, welfare, religion and parties. This KKM student completed training in Cibatu Village, Cikembar District, Kab. Sukabumi. Residents of Cibatu Village generally invite the emergence of students to make changes through strengthening areas that work together